Three decades of heart transplantation: experience and long-term outcome. (31st December 2022) - Nelson, Lærke Marie; Rossing, Kasper; Boesgaard, Søren; Møller-Sørensen, Hasse; Møller, Christian Holdflod; Gustafsson, Finn; Olsen, Peter Skov
Abstract: Objectives . Heart transplantation (HTx) has become an established treatment option in patients with end-stage heart failure. The aim of this study was to report on long-term outcome over the past three decades. Design . Consecutive adult patients receiving first-time and isolated HTx from October 3, 1990, to November 2, 2020, at Rigshospitalet, Copenhagen, Denmark, were retrospectively evaluated. Data were obtained from the Scandinavian Transplant Registry and patient medical records. Recipients were grouped by time of transplantation ( early era : 1990–1999; mid era : 2000–2009; recent era : 2010–2020). Results . A total of 384 recipients (77% men, median age 50 [IQR: 40–57]) were included. Median number of HTx procedures per year was 12 (10–14). Overall, 22% of patients were bridged to HTx with a mechanical circulatory support device. Median survival for the whole cohort was 13.8 years and improved numerically from the early era (12.6 years) to the mid era (14.9 years). Median survival conditional on survival to 1-year follow-up after HTx was 16.1 years. Survival probability by Kaplan–Meier method improved significantly from the mid to the recent era (log-rank p = .02). Conclusions . Heart transplantation remains an excellent treatment for selected patients with end-stage heart failure and long-term outcome has improved significantly over the past decades.